2021
DOI: 10.2196/28716
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Public Response Associated With Various COVID-19 Restrictions in Ontario, Canada: Observational Infoveillance Study Using Social Media Time Series Data

Abstract: Background News media coverage of antimask protests, COVID-19 conspiracies, and pandemic politicization has overemphasized extreme views but has done little to represent views of the general public. Investigating the public’s response to various pandemic restrictions can provide a more balanced assessment of current views, allowing policy makers to craft better public health messages in anticipation of poor reactions to controversial restrictions. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Although individual protective measures were rather consensual in our study population, collective restrictions had more mixed acceptance rates—ranging from 80%-57%. One possible explanation is that these measures were assessed in light of their restrictive nature [ 31 ], socioeconomic consequences (eg, unemployment, bankruptcy of businesses, mobility restrictions), and/or psychological burden (eg, anxiety, depression) [ 32 ]. For instance, the stay-at-home order for nonessential workers was linked to health anxiety, financial worry, decreased physical activity, isolation, and loneliness [ 9 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although individual protective measures were rather consensual in our study population, collective restrictions had more mixed acceptance rates—ranging from 80%-57%. One possible explanation is that these measures were assessed in light of their restrictive nature [ 31 ], socioeconomic consequences (eg, unemployment, bankruptcy of businesses, mobility restrictions), and/or psychological burden (eg, anxiety, depression) [ 32 ]. For instance, the stay-at-home order for nonessential workers was linked to health anxiety, financial worry, decreased physical activity, isolation, and loneliness [ 9 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a view of Nova Scotians’ experiences with the COVID-19 pandemic PHM. Despite limitations, qualitative findings from our participants showed that overall, many Nova Scotians favoured following provincially mandated PHM rather than more individualistic libertarian conduct expressed in some other pockets of the country (Chum et al, 2021 ; Lang et al, 2021 ). Importantly, Nova Scotians relied on trusted COVID-19 information sources, considered to be independent of politics and social media.…”
Section: Discussionmentioning
confidence: 75%
“…However, it is difficult for humans to understand numeric sentiment scores. Therefore, the compound sentiment scores are categorized as “positive” if they are equal or greater than +0.05, “negative” if they are equal to or lower than −0.05 and “neutral” if neither based on prior research [ 27 ].…”
Section: Methodsmentioning
confidence: 99%